2017
DOI: 10.1097/mpg.0000000000001606
|View full text |Cite
|
Sign up to set email alerts
|

NASPGHAN Clinical Report on Postoperative Recurrence in Pediatric Crohn Disease

Abstract: Pediatric Crohn disease is characterized by clinical and endoscopic relapses. The inflammatory process is considered to be progressive and may lead to strictures, fistulas, and penetrating disease that may require surgery. In addition, medically refractory disease may be treated by surgical resection of inflamed bowel in an effort to reverse growth failure. The need for surgery in childhood suggests severe disease and these patients have an increased risk for recurrent disease and potentially more surgery. Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 112 publications
3
32
0
Order By: Relevance
“…In our study, gender was not associated with POR risk, similar to studies in adults with CD 2,14–16 . There was a trend towards women having a higher recurrence rate, consistent with previous studies in pediatric CD 28,29 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In our study, gender was not associated with POR risk, similar to studies in adults with CD 2,14–16 . There was a trend towards women having a higher recurrence rate, consistent with previous studies in pediatric CD 28,29 .…”
Section: Discussionsupporting
confidence: 92%
“…In our study, gender was not associated with POR risk, similar to studies in adults with CD. 2,[14][15][16] There was a trend towards women having a higher recurrence rate, consistent with previous studies in pediatric CD. 28,29 We found that there was no significant difference in mean age of diagnosis between the recurrence and nonrecurrence CD patients.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…[1][2][3] Similar rates are seen in studies evaluating only pediatric onset Crohn's disease. 4 Furthermore, both referral center and population-based studies suggest that there has been minimal to no decrease in the rate of Crohn's disease surgery since the introduction of biologic agents. 3 Unfortunately, such surgery is usually not curative as Crohn's disease typically recurs at some point in the postoperative course with anywhere from 35 to 70% of patients requiring repeat surgery within 10 years.…”
mentioning
confidence: 99%
“…Pediatric IBD patients should be screened frequently for these disorders, as well as for impairments in social functioning, and referred appropriately [13]. A surgeon should be consulted for those who fail medical management or have disease-related complications that require it, such as dysplasia, perforations, and obstructions [14,15].…”
Section: Multidisciplinary Approachmentioning
confidence: 99%